Stability and efficacy of green solvent and natural excipient-based semisolid formulations compared with conventional formulations: a review - Muh Fajar Fauzi; Eko Hidayaturrohman Khumaini (Pharmacy Reports, 2025)
Semisolid dosage forms, including creams, gels, ointments, hydrogels, and emulgels, are widely used for topical drug delivery. Green solvent- and natural excipient-based systems have gained attention for their potential biocompatibility and reduced environmental burden, but their stability advantages over conventional formulations remain unclear. This systematic review with narrative synthesis evaluated 36 eligible studies from 1,000 records. Due to the methodological and clinical heterogeneity of the included studies, a narrative synthesis was conducted in place of quantitative pooling. Among 20 studies reporting direct comparative efficacy, 11 showed superior results for green or natural formulations, 7 reported equivalence, and 2 had mixed findings. Safety outcomes were generally comparable or more favorable for green formulations, with no serious adverse events linked to these systems. However, stability evidence was limited: only 9 studies reported stability-related parameters, and long-term or accelerated data were largely absent. While green solvent- and natural excipient-based semisolid formulations demonstrate promising efficacy and tolerability, current evidence does not establish that they are inherently more stable than conventional systems, and their translational readiness remains constrained by insufficient demonstration of reproducible formulation quality over time.